1980
DOI: 10.1677/joe.0.0860363
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Glucocorticoids in the Development of Insulin Resistance After Ischaemic Limb Injury in the Rat

Abstract: Bilateral hind-limb ischaemia in the rat is known to cause insulin resistance, as shown by a sustained rise in plasma glucose concentration with a decreased metabolic clearance rate but no fall in plasma insulin. However, when the concomitant rise in the plasma concentration of corticosterone was diminished by an inhibitor of its biosynthesis, trilostane (WIN 24 540), the hyperglycaemia became transient. The mechanism of this effect has now been studied by measuring the rate of disappearance of [5-3H,U-14C]glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
1
1

Year Published

1981
1981
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
2
4
1
1
Order By: Relevance
“…Values (Fig. 4) were higher in women than in men at ISS 4-8 (P<0.05) and [9][10][11][12][13][14] (P < 0.005), as expected,11 and rose with time after injury at ISS [4][5][6][7][8][9][10][11][12][13][14] [adrenaline] had been measured in them. The residuals were, however, very non-normally distributed.…”
Section: Preliminary Observationssupporting
confidence: 62%
See 2 more Smart Citations
“…Values (Fig. 4) were higher in women than in men at ISS 4-8 (P<0.05) and [9][10][11][12][13][14] (P < 0.005), as expected,11 and rose with time after injury at ISS [4][5][6][7][8][9][10][11][12][13][14] [adrenaline] had been measured in them. The residuals were, however, very non-normally distributed.…”
Section: Preliminary Observationssupporting
confidence: 62%
“…2), which were measured within the fairly narrow bands of injury severity shown. These, suggested by Copes et al,13 correspond to minor (ISS 1-3), moderate (4)(5)(6)(7)(8), severe (9)(10)(11)(12)(13)(14), very severe (16)(17)(18)(19)(20)(21)(22)(23)(24) and life-threatening (25+) injuries. Success has been measured by the percentage of the variance within each group that can be accounted for by the various factors.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Glucagon and cyclic AMP, the latter in a HC104 extract of freeze-clamped liver, were measured according to the instructions with the kits referred to above, except that 1251 measurements were made in a y-counter, and glucagon extracts were dried in a stream of N2 instead of in a desiccator. Insulin was measured by a single-antibody technique (Barton & Passingham, 1980), corticosterone as described by Nicholson & Van Loon (1973), plasma lactate as described by Heath & Rose (1985), and plasma glucose according to the instructions with the kit.…”
Section: Methodsmentioning
confidence: 99%
“…[It is thought by some (Alberti & Johnston, 1977) that the active involvement of cortisol in the responses to injury can continue for some time after the 'ebb' phase.] Experiments on rats (Barton & Little, 1978;Barton & Passingham, 1980;1982) have shown that increased glucocorticoid secretion is necessary to maintain the hyperglycaemia of injury and that the adrenal plays an important part in the compensation for the fluid loss associated with limb ischaemia but not with haemorrhage. The reason for this difference is not yet known but inhibition of glucocorticoid secretion in the rat by trilostane increases the mortality after limb ischaemia.…”
Section: Responses Which Vary With the Severity Of Injurymentioning
confidence: 99%